Decisional capacity for advanced care directives in Parkinson's disease with cognitive concerns. (June 2017) - Abu Snineh, Muneer; Camicioli, Richard; Miyasaki, Janis M.
Abstract: Introduction: Physician Orders for Life Sustaining Therapies (POLST) or Goals of Care (GOC) are legal documents to guide intensity of interventions (ICU, resuscitation, hospitalization or comfort care) completed by healthcare professionals following counseling of patients or their designated medical decision makers. Capacity (understanding, appreciation, reasoning and expressing a choice) to consent to POLST or GOC has not been determined among Parkinson's disease (PD) patients. We sought to assess GOC PD decisional capacity for those with cognitive complaints but not dementia. Methods: Fifty consecutive PD patients were recruited from the Movement Disorders Program. Mini Mental Status Examination (MMSE), Montreal Cognitive Assessment (MoCA) and the MacArthur Competency Assessment Test (MacCAT) for GOC were administered. Results: Mean MMSE and MOCA was 27.76 and 24.5 respectively. Twenty subjects had impaired executive function. MacCAT correlated with MoCA and MMSE (p < 0.001, 0.001) but despite impaired understanding, appreciation and reasoning among some subjects, all subjects expressed a choice. Conclusions: This exploratory study demonstrates PD with cognitive concerns had a range in decisional capacity with lower MoCA and MMSE scores predicting impaired MacCAT subscores. Clinicians should be aware that cognitive complaints without dementia may impact capacity. Despite impairments in understanding, appreciation or reasoning, patients may still express a choice. Hence, a choice in this setting may not represent their true values and goals. GOC discussions require explicit determination of the domains of capacity. Discussions regarding GOC should occur early in the course of PD. Highlights: Physician Orders for Life Sustaining Therapies (POLST) or Goals of Care (GOC) are legal forms of advance care directives. Decisional capacity requires understanding, appreciation, reasoning and expressing a choice congruent with appreciation and reasoning. Non-demented PD patients with cognitive complaints had a range of understanding, appreciation and reasoning but all expressed a choice. Those with executive dysfunction were more likely to have impairments in decisional capacity. POLST or GOC discussions should occur early in the course of PD and better communication tools are required to guide these crucial conversations.